PENGARUH PENDEKATAN MELALUI KONSELING INTERPERSONAL TERHADAP RESPON SOSIAL, EMOSIONAL DAN SPIRITUAL PADA PASIEN HIV/AIDS - Jayani, Indah; Ruffaida, Fatma Sayekti (Universitas Tribhuwana Tunggadewi, 2020)
Approach to PLWHA by providing interpersonal counseling is the right thing to do to overcome psychological problems including social, emotional and spiritual aspects of PLWHA. This study aims to look at the effect of interpersonal counseling on social, emotional and spiritual responses in HIV/ AIDS patients. This research is a type of non-experimental research with a cross-sectional approach. The sample is post-test people and tested positive for HIV in the Kediri region, which is 32 with purpossive sampling technique. Data on social, emotional and spiritual responses were obtained based on the results of data recapitulation from the instrument in the form of a questionnaire. The results of the study with the non-parametric Wilcoxon test showed there were differences between social responses of HIV/AIDS patients before and after given interpersonal counseling with p value = 0,000, there were differences between the emotional responses of HIV/AIDS patients before being given interpersonal counseling and after being given counseling with p value = 0,000, and there is a difference between spiritual responses in HIV/AIDS patients before being given interpersonal counseling and after being given interpersonal counseling with p value = 0,000. It can be concluded that interpersonal counseling influences social, emotional and spiritual responses of HIV/AIDS patients. It is recommended that the mentoring of HIV/AIDS patients through interpersonal counseling can continue so as to enhance physiological responses that will have an impact on disease prognosis, prevention of opportunistic infections and reduce mortality rates for HIV patients/ AIDS.